Connective thinking on building envelope – Human body exergy analysis. (November 2015) - Dovjak, Mateja; Shukuya, Masanori; Krainer, Aleš
Highlights: Interactions between building systems and human body are examined with exergy analysis. Thermal exergy flows through the building envelope are analysed with human body exergy balance. Thermal insulation reduces exergy consumption rate within building systems in all climates. Thermal insulation has important benefits on each component of the human body exergy balance. Connective thinking enables quantitative evaluation of comfort and healthy conditions. Abstract: The purpose of this paper is to analyse the efficiency of building interventions both from building and user point of view. With exergy analysis based on the connective thinking approach, thermal exergy flows through the building envelope are analysed jointly with human body exergy balance. Two cases of building envelope systems, thermally well-insulated case and thermally non-insulated case, are located at four typical climates (temperate, cold, hot/dry, hot/humid). "Warm" and "cool" exergies transferred by radiation, convection and conduction at the interior surface of an envelope are calculated with methodology developed by Shukuya (2013) [7, 35]. Human body exergy balance (hBExB) is calculated with software developed by Asada (2010) [6]. Results show that thermal insulation significantly reduces the exergy consumption rate (ExCr) within building envelope systems in all climates. Additionally, it allows the interior surfaces of building envelope to emit "warm" radiant exergy into the room space in temperate and cold climates, while on the other hand to emit "cool" radiant exergy instead of "warm" radiant exergy in hot/dry and hot/humid climates. Thermal insulation has important benefits on hBExB in all climates; it decreases human body exergy consumption rate (hbExCr) due to lower input exergy and higher output exergy. Exergy analysis based on the connective thinking approach helps us to understand all interactions between building systems and human body and consequently approach to the quantitative evaluation of comfort and healthy living and working conditions.